2020
DOI: 10.1186/s12879-020-04992-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation of coxsackieviruses A-6, A-10, and A-16 causes hand, foot, and mouth disease in Guangzhou city, China

Abstract: Background: Hand, foot, and mouth disease (HFMD) is a common infectious disease occurring in children under 5 years of age worldwide, and Enterovirus A71 (EV-A71) and Coxsackievirus A16 (CVA-16) are identified as the predominant pathogens. In recent years, Coxsackievirus A6 (CVA-6) and Coxsackievirus A10 (CVA-10) have played more and more important role in a series of HFMD outbreaks. This study aimed to understand the epidemic characteristics associated with HFMD outbreak in Guangzhou, 2018. Methods: The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 54 publications
2
25
0
1
Order By: Relevance
“…Data coincide with those observed in template countries for EV infections overall, including Spain, although the autumn peak is usually not as pronounced [ 22 , 26 , 30 ]. They are also similar to those described in a study conducted in China [ 39 ], in which cases of HFMD by CVA6 seem to have a characteristic peak in autumn–winter that in Spain can be associated with the beginning of the school year.…”
Section: Discussionsupporting
confidence: 89%
“…Data coincide with those observed in template countries for EV infections overall, including Spain, although the autumn peak is usually not as pronounced [ 22 , 26 , 30 ]. They are also similar to those described in a study conducted in China [ 39 ], in which cases of HFMD by CVA6 seem to have a characteristic peak in autumn–winter that in Spain can be associated with the beginning of the school year.…”
Section: Discussionsupporting
confidence: 89%
“…The other small peak was noticed in the months of January and November in the year 2018, and probably it could be explained due to the cold climatic conditions. Similar observations were noticed from other countries including India 22,37,38 . The explanation for seasonality of these cases is unclear, however, it could be explained that the climatic conditions such as high humidity and cold weather might have been contributed to the increase in the occurrence of HFMD incidence 39 …”
Section: Discussionsupporting
confidence: 77%
“…In future research, we can consider nationwide data collection to further explore the main meteorological factors related to the transmissibility of HFMD. Related studies have also shown that the main pathogens of HFMD change in different seasons and years, as well as a high mutation rate of human enterovirus (38,39). Besides, as current research on the temperature threshold of transmissibility is relatively limited, there is no unified threshold judgment standard.…”
Section: Discussionmentioning
confidence: 99%